Preliminary Design of Monitoring System of ITER Static Magnetic Field Test Facility. Issue 1 (April 2021) - Pan, Mi; Gao, Ge; Wang, Linsen; Wang, Shusheng
Abstract: The structure and characteristics of the ITER static magnetic field test facility is introduced. The preliminary design scheme of the monitoring system of the facility is proposed. According to the characteristics of the facility that it includes several subsystems, multiple signal types and is suffered from electromagnetic interference, the solution given combines NI CompactRIO embedded system, NI PXIe and Ethernet exchange technology. It can realize signal acquisition, status monitoring, safety interlock, parameter setting and other function. Also, the scheme covers the methods to weaken the interference from the surrounding magnetic field on the system itself and improve the stability of the system. The preliminary design scheme complies with control, data acquisition and communication specifications from ITER, and meets the SIL level assessment requirements in the concept phase.